Investment home bias in the European Union - Martins, António (2020)
The creation of the European Single Market (ESM) and the adoption of the Euro eliminated barriers for capital mobility. This paper analysis the dependency of investment on domestic savings across European Union (EU) economies over three diﬀerent time frames split by major milestones in the economic history of the union. Using a panel error correction model, I ﬁnd evidence of low capital mobility before the creation of the ESM and after the crisis of 2008, suggesting that a solvency constraint can bind investment to domestic savings even when barriers for capital mobility are eliminated. The estimates suggest that there is a long-run relationship between the aforementioned aggregates associated with a solvency constraint. However, this constraint does not appear to be binding between 1993 and 2007, matching with an increased spread in the current account balances between high and low income economies among the EU. Between 2007 and 2020, restrictions on borrowing faced by some EU economies reduced capital mobility, despite the absence of capital controls and exchange rate risk.